Komparasi Efisiensi Bank Umum Syariah dan Bank Umum Konvensional di Indonesia Dengan Menggunakan Teknik Data Envelopment Analysis Periode 2012-2015 - Putri Chintia Latifa; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this study is to determine there is a difference of efficiency in terms of income and intermediation between shariah banks and conventional banks during 2012-2015. Efficiency is a measure of bank performance which describes the optimal output level conditions with the level of the current input. The measurement of efficiency in this study usesDEA with CRS assumption. This study uses 22 shariah banks and conventional banks which are the same size in terms of core capital, grouped based on corresponding business activities banks group (BUKU). Then, they are tested by using different independent sample t-test andMann-Whitney Test. Financial performance assessment for the banks uses four input variables and four output variables. A comparative analysis conducted showed that there were no differences in the efficiency of shariah banks and conventional banks. While on the intermediation there are significant differences between the two groups of banks.